1999
DOI: 10.1016/s0741-5214(99)70013-3
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization during venous thrombosis organization: A preliminary study

Abstract: This study shows that thrombus organization involves neovascularization and that IL-8 augments thrombus organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 17 publications
4
133
0
2
Order By: Relevance
“…Histological studies have confirmed the appearance of intrathrombus clefts and neovascular channels that evolve mostly within the first 4 wk (7,18,20). Pleotropic angiogenic growth factors released by polymorphonuclear neutrophils (PMNs) and monocytes are known to be present in the resolving thrombus and include vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) (21)(22)(23).…”
Section: Eep Vein Thrombosis (Dvt)mentioning
confidence: 94%
See 3 more Smart Citations
“…Histological studies have confirmed the appearance of intrathrombus clefts and neovascular channels that evolve mostly within the first 4 wk (7,18,20). Pleotropic angiogenic growth factors released by polymorphonuclear neutrophils (PMNs) and monocytes are known to be present in the resolving thrombus and include vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) (21)(22)(23).…”
Section: Eep Vein Thrombosis (Dvt)mentioning
confidence: 94%
“…Restoration of blood flow in a thrombosed vein also involves neovascularization with functional flow channels, thrombus retraction, and fibrinolysis (7,18,19). Histological studies have confirmed the appearance of intrathrombus clefts and neovascular channels that evolve mostly within the first 4 wk (7,18,20).…”
Section: Eep Vein Thrombosis (Dvt)mentioning
confidence: 95%
See 2 more Smart Citations
“…Wakefield et al reported the results of on an experimental study that suggested that neoangiogenesis occurs during the process of organization of a thrombus, resulting in recanalization of occluded vessels 30 . Along the same lines, other authors have claimed that recanalization is part of the physiological process of thrombus remodeling.…”
Section: Recanalization and Neoangiogenesismentioning
confidence: 99%